The Influence of Educational Interaction and Reward and Punishment on Islamic Religious Education Learning Outcomes - Nurhasanah Nurhasanah; Sunarto Sunarto; Siti Roudhotul Jannah (CV. Bimbingan Belajar Assyfa, 2025)
This research is motivated by the low learning outcomes of students in Islamic Religious Education subjects, which is suspected to be related to the less-than-optimal educational interaction and the implementation of reward and punishment in the classroom. This study aims to analyze the effect of educational interaction and reward and punishment on student learning outcomes, both partially and simultaneously. The research employed a quantitative approach with a survey method. The population consisted of all seventh-grade students of SMP Negeri 1 Kotaagung Timur, Tanggamus Regency, totaling 52 students, who also served as the sample (total sampling). Data were collected using questionnaires for the variables of educational interaction and reward and punishment, and documentation of scores for learning outcomes. Data analysis used multiple linear regression. The results showed that partially, educational interaction had a positive and significant effect on learning outcomes (t count = 3.25 > t table = 2.01), as did reward and punishment (t count = 2.98 > t table = 2.01). Simultaneously, both variables also had a significant effect (F count = 39.87 > F table = 3.19) with a contribution of 62% (R² = 0.62). Thus, improving the quality of educational interaction and the appropriate application of reward and punishment can enhance students' PAI learning outcomes.